2001
DOI: 10.1645/0022-3395(2001)087[0536:ccitso]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Corynosoma cetaceumin the Stomach of Franciscanas,Pontoporia blainvillei(Cetacea): an Exceptional Case of Habitat Selection by an Acanthocephalan

Abstract: Adult acanthocephalans are typically found in the intestine of vertebrates, where they can readily absorb nutrients. However, Corynosoma cetaceum has been frequently reported in the stomach of cetaceans from the Southern Hemisphere. The ecological significance of this habitat was investigated by examining data on number, sex ratio, maturity status, biomass, and fecundity of C. cetaceum in different parts of the digestive tract of 44 franciscanas Pontoporia blainvillei. Individual C. cetaceum occurred in the py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 23 publications
0
17
2
Order By: Relevance
“…The acanthocephalan C. cetaceum is known to infect mainly the pyloric stomach of P. blainvillei (Aznar et al 1995, Andrade et al 1997. In the present study, C. cetaceum had lower prevalence and mean intensity of infection levels than those reported for the southern coast of RS (Andrade et al 1997) (Tables 4 and 5), Uruguay and Argentina (Aznar et al 1995(Aznar et al , 2001. Possibly, these observed differences are related to a low availability of intermediate hosts for this parasite in the northern RS.…”
Section: Discussioncontrasting
confidence: 64%
“…The acanthocephalan C. cetaceum is known to infect mainly the pyloric stomach of P. blainvillei (Aznar et al 1995, Andrade et al 1997. In the present study, C. cetaceum had lower prevalence and mean intensity of infection levels than those reported for the southern coast of RS (Andrade et al 1997) (Tables 4 and 5), Uruguay and Argentina (Aznar et al 1995(Aznar et al , 2001. Possibly, these observed differences are related to a low availability of intermediate hosts for this parasite in the northern RS.…”
Section: Discussioncontrasting
confidence: 64%
“…Direct biomass estimates of the specimens were used as a benchmark for the other methods, enabling quantifying the error associated with indirect methods. Mean biomass was estimated using the method described in the literature 16 . Since specimens had been stored in 70° ethanol for 10–30 years, they were placed in 0.9% saline solution (9 g NaCl per 1 L distillated water) for 1 to 5 days to allow the tissues to re-hydrate.…”
Section: Methodsmentioning
confidence: 99%
“…Invertebrates are often the cornerstone of ecosystems 12 , 13 and recent studies have shown that their biomass is greater than that previously thought 14 , 15 . Different methods have been proposed to study the allocation of biomass between various taxonomic groups of invertebrates, mostly arthropods, but also considered groups include sponges, cnidarians, platyhelminths, annelids, acanthocephalans, nematodes, molluscs, nemerteans, echinoderms, bryozoans and urochordates have been considered 14 , 16 24 . As direct measurements of biomass of small invertebrates (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Trunk length, disk diameter, and body volume (assuming a conical shape) of these specimens were measured following Hernández-Orts et al [ 46 ]. Fecundity was estimated as the number of acanthors per female [ 47 ] in 10, 30 and 30 gravid females, randomly selected, from 4 penguins, 3 sea lions and 4 fur seals, respectively. The contents of each worm were washed into a beaker and the volume made up to 10 ml, then continually agitated using a magnetic stirrer for at least 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Fully developed eggs were distinguished by having a completely formed acanthor inside. Mean numbers of each egg type obtained from these samples were then extrapolated to the total volume [ 47 ].…”
Section: Methodsmentioning
confidence: 99%